ANALISIS DISIPLIN DAN BUDAYA KERJA ISLAM PADA LEMBAGA AMIL ZAKAT INFAQ DAN SADAQAH MUHAMMADIYAH (LAZISMU) KOTA MEDAN - Nitia Mantasya (STAI Syekh.H. Abdul Halim Hasan Al Ishlahiyah Binjai, 2022)
The problem in this study is the lack of punctuality in working at the Amil Zakat Infaq and Sadaqah Muhammadiyah Institute (LAZISMU) Medan City. Lack of compliance with regulations that have been determined by the Amil Zakat Infaq and Sadaqah Muhammadiyah Institute (LAZISMU) Medan City. Lack of communication between superiors and subordinates in the Amil Zakat Infaq and Sadaqah Muhammadiyah Institute (LAZISMU) Medan City. The purpose of the study was to determine work discipline and Islamic work culture at the Amil Zakat Infaq and Sadaqah Muhammadiyah Institute (LAZISMU) Medan City. to find out the Islamic work culture at the Amil Zakat Infaq and Sadaqah Muhammadiyah Institute (LAZISMU) Medan City. This study uses a qualitative approach. The results show that the results of the research the authors get regarding work discipline at Lazismu are that there are still many members of the organization who are often late to work according to the work schedule, and are often not in place so that it seems that there is a lack of a sense of responsibility for members in working at Lazismu, Medan City. Based on the organizational culture in Lazismu, Medan City has prime patterns in the fourth value, namely professionalism, which contains 'competent and responsible' and 'work smart and thorough' behaviors and has applied the principles of the Prophet's commendable attitude, one of which is siddiq, tabliqh, amanah, fathonah, and istiqomah. Obstacles faced by the Amil Zakat Infaq and Sadaqah Muhammadiyah Institute (LAZISMU) Medan City, namely leaving work or office duties Employees leaving the office without reason or permission to superiors, so that office work, Abusing rights and authority or responsibilities experience obstacles in carrying out discipline despite the level of obstacles it's small.